2001
DOI: 10.1007/s00417-001-0377-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of postoperative axial length growth and intraocular pressure in congenital glaucoma – a retrospective study in trabeculotomy and goniotomy

Abstract: The data show remarkably good correlation of postoperative IOP with postoperative axial length growth. Axial length measurements can therefore help to ascertain halting or progression of congenital glaucoma and thus are considered an important parameter for congenital glaucoma follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 35 publications
3
39
1
Order By: Relevance
“…The normal axial length development within the first decade of life was published by Buschmann [5], Sampaolesi [31], and Haigis [16]. We found that axial length growth can continue after surgery, either accelerated or parallel to the normal curve, or can halt [19]. Law et al [21] reported a reduction in axial length in 3 out of 10 eyes and no decrease of axial length in 7 out of 10 eyes, but the axial length pattern paralleled the normal growth curve.…”
Section: Discussionmentioning
confidence: 62%
“…The normal axial length development within the first decade of life was published by Buschmann [5], Sampaolesi [31], and Haigis [16]. We found that axial length growth can continue after surgery, either accelerated or parallel to the normal curve, or can halt [19]. Law et al [21] reported a reduction in axial length in 3 out of 10 eyes and no decrease of axial length in 7 out of 10 eyes, but the axial length pattern paralleled the normal growth curve.…”
Section: Discussionmentioning
confidence: 62%
“…Axial length has also been known to be closely correlated with increasing IOP in the postoperative period in eyes with congenital glaucoma. 13 Compared with control eyes, the lens in congenital glaucoma eyes was much smaller. Sampaolesi and Caruso 3 also found the lens to be smaller in eyes with congenital glaucoma compared with the lens in normal infants.…”
Section: Discussionmentioning
confidence: 97%
“…19,21 Trabeculotomy and goniotomy are the most common types of surgical procedures. 14,15,21 In our cohort, trabeculotomy was the primary surgical treatment, as the incidence of corneal edema was high, making difficult the angle view and thereby goniotomy.…”
Section: Discussionmentioning
confidence: 99%